2015
DOI: 10.1007/s00041-015-9431-0
|View full text |Cite
|
Sign up to set email alerts
|

Phase Retrieval from Gabor Measurements

Abstract: Abstract. Compressed sensing investigates the recovery of sparse signals from linear measurements. But often, in a wide range of applications, one is given only the absolute values (squared) of the linear measurements. Recovering such signals (not necessarily sparse) is known as the phase retrieval problem. We consider this problem in the case when the measurements are time-frequency shifts of a suitably chosen generator, i.e. coming from a Gabor frame. We prove an easily checkable injectivity condition for re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 27 publications
2
43
0
Order By: Relevance
“…In this case, the magnitude of the STFT determines the underlying signal uniquely under mild conditions. This conclusion was already derived in [11] based on different considerations. Nevertheless, the following proposition comes with an explicit recovery scheme as presented in Appendix A.…”
Section: Uniqueness and Basic Algorithmssupporting
confidence: 52%
“…In this case, the magnitude of the STFT determines the underlying signal uniquely under mild conditions. This conclusion was already derived in [11] based on different considerations. Nevertheless, the following proposition comes with an explicit recovery scheme as presented in Appendix A.…”
Section: Uniqueness and Basic Algorithmssupporting
confidence: 52%
“…This case resembles the FROG setup, where a known reference window replaces the unknown shifted signal. Several works derived uniqueness results for this case under different conditions [15,17,18,19]. In [16] it was shown that, roughly speaking, it is sufficient to set L ≈ N/2 (namely, 2N measurements) to determine almost all non-vanishing signals.…”
Section: Frog Recoverymentioning
confidence: 99%
“…It is now known that by choosing windows with appropriate properties, only a small redundancy in the measurements (i.e. short windows) is needed to enforce uniqueness (for details, see [14], [15], [16], [17], [10]). The STFT of a 1D signal x ∈ C N with respect to a real sliding window g of length W is defined as where k = 0, .…”
Section: Introductionmentioning
confidence: 99%